Circadian blood pressure profile and myocardial hypertrophy in patients with renal arterial hypertension - E. Kh. Akhmetzyanova; G. R. Altynbaeva; A. S. Akhmetzyanov; Yu. M. Latyshev (Российский кардиологический журнал, 2007)
The authors discuss the role of renal arterial hypertension etiology (chronic glomerulonephritis, chronic pyelonephritis) in myocardial hypertrophy development and the association between 24-hour blood pressure monitoring parameters and left ventricular myocardial mass.